Creating 3D Animations for Seasonal Flood Education - Ramadhani, Amanda Putri Ramadhani; Maulina, Riska; Delakamin, Putri Ika; Sabrila, Trifebi Shina (INSTALL: Information System and Technology Journal, 2025)
Seasonal flooding is a routine problem in Banjarmasin City which is triggered by high rainfall and poor waste management. The lack of public awareness in maintaining environmental cleanliness has also worsened this condition. This research aims to develop educational media in the form of 3D animations that explain the causes, impacts, and solutions of seasonal floods. The production method includes three main stages: pre-production, production, and post-production, using the Blender software as well as the BlenderKit add-on. The final result is in the form of an educational animation video that describes the process of flooding and preventive actions that can be taken by the community. Preliminary evaluations show that these animations are effective in conveying educational messages and raising environmental awareness. This media is expected to support environmental campaigns by the government and educational institutions.